2001
DOI: 10.1097/00041327-200103000-00007
|View full text |Cite
|
Sign up to set email alerts
|

A Girl Without a Chiasm: Electrophysiologic and MRI Evidence for the Absence of Crossing Optic Nerve Fibers in a Girl With a Congenital Nystagmus

Abstract: An otherwise healthy 15-year-old girl with a congenital nystagmus was evaluated at our department using visual evoked potential recording and magnetic resonance imaging. She appears to have the unique isolated inborn absence of the optic chiasm, described only once before in two unrelated girls. Unlike these previously described cases, our patient does not seem to display a see-saw nystagmus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 8 publications
5
31
0
Order By: Relevance
“…Alternating esotropia and vertical tropias were also documented. A similar case of isolated congenital achiasmia was documented in another 15-year-old girl, but in her case there was only a predominantly horizontal nystagmus, without evidence of a see-saw component (Jansonius et al 2001). See-saw nystagmus was observed in a separate case report involving a 4-month-old female infant with achiasmia, but this patient also had associated brain abnormalities including midline craniofacial cleft lip and nasoethmoidal encephalocele (Leitch et al 1996).…”
Section: Introductionmentioning
confidence: 57%
“…Alternating esotropia and vertical tropias were also documented. A similar case of isolated congenital achiasmia was documented in another 15-year-old girl, but in her case there was only a predominantly horizontal nystagmus, without evidence of a see-saw component (Jansonius et al 2001). See-saw nystagmus was observed in a separate case report involving a 4-month-old female infant with achiasmia, but this patient also had associated brain abnormalities including midline craniofacial cleft lip and nasoethmoidal encephalocele (Leitch et al 1996).…”
Section: Introductionmentioning
confidence: 57%
“…Apkarian et al (1995) reported on two achiasmatic children suffering from low vision, nystagmus, and advanced concentric visual field defects. A more recent study (Jansonius et al, 2001) reported a further achiasmatic person with marked opthalmological symptoms including nystagmus, reduced visual acuity, and massive visual-field defects. A recent study performed with 12 patients with renal coloboma syndrome detected mutations in the Pax-2 gene and ocular abnormalities within both the retina and the optic nerve (Dureau et al, 2001).…”
Section: Clinical Manifestation Of Pax-2 Defectsmentioning
confidence: 97%
“…It is, therefore, not surprising that malformations of the chiasm are also found in human syndromes that affect the visual system. Apkarian et al [3] and Jansonius et al [32] reported on three achiasmatic children suffering from low vision, nystagmus and advanced concentric VFDs. Apkarian et al [2] described misrouting of retinofugal fibres in neonates with albinism.…”
Section: Neuroanatomical Considerationsmentioning
confidence: 99%